Gratification Disorder: A Case Report from the Himalayan Country–Nepal - Pawan Sharma; Omkar Dhungel; Lokesh Saini (Journal of Psychosexual Health, 2023)
The gratification disorder is common in children between the ages of 3 months and 3 years. The condition is called a “disorder,” but it is a normal behavioral variant in early childhood. The common differentials for this condition are childhood epileptic seizures. The failure to recognize this case may lead to unnecessary investigations and inappropriate treatment. It improves with age, generally by reassuring the anxious parents. In this case report, we present a case of a 2-year-old female child with a history of episodic rocking of the hip and scissoring of lower limbs, and she was treated with anti-epileptics but showed no improvement. After detailed assessment and normal investigations, a diagnosis of gratification disorder was made. The parents were psycho-educated and assured. Though reluctant to accept the diagnosis, they complied with the advice of ignoring the events and distracting the child. This was a challenging case for both the clinicians to diagnose and the parents to accept the diagnosis.